How is the Implementation of Governance at the National Amil Zakat Agency of Barito Kuala Regency - Rizky Fadhillah; Mauizhatil Hasanah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research examines the governance of the National Amil Zakat Agency of Barito Kuala Regency as an effort to optimize transparent, professional, and sharia-compliant zakat management. Although South Kalimantan has the highest zakat potential in Kalimantan Island, its zakat realization is still far from the target, reflecting the challenges of public trust and the effectiveness of the institution's governance. This study aims to evaluate the governance of Barito Kuala National Amil Zakat Agency using three main indicators: Zakat Core Principles Index, Sharia Compliance Index of Zakat Management Organization, and Financial Ratio Analysis. Using a qualitative-descriptive approach, data was collected through observation and internal document analysis. The result shows that the implementation of Zakat Core Principle scores 0.44 (good enough category), while sharia compliance scores 0.72 (good category), and financial ratio shows high efficiency and effectiveness in collecting and distributing zakat. Important findings reveal that the suboptimal documentation of Operational Procedur Standard, absence of internal audit, and high operational burden become obstacles to ideal governance. Although the management of zakat in Barito Kuala National Amil Zakat Agency has been running according to regulations and sharia principles, improvement of institutional structure, documentation, efficiency of human resources, and transparency of financial statements are needed. This research provides a practical contribution as an internal evaluation of the institution and a scientific contribution in the development of accountable and sustainable zakat management in Indonesia.